(untitled) (Modern American Journal of Social Sciences and Humanities, 2026)
This article analyzes the concept of social mentality and its role in the development of society from a socio-philosophical perspective. The study examines the main factors influencing the transformation of social mentality, including socio-economic, political-legal, spiritual-educational, information-communication, and historical-cultural factors. It is argued that the harmonious combination of national values, historical memory, and modern reforms plays an important role in the renewal of social mentality.